2014
DOI: 10.1038/eye.2013.281
|View full text |Cite
|
Sign up to set email alerts
|

Anterior segment OCT imaging in mucopolysaccharidoses type I, II, and VI

Abstract: Purpose To describe the anterior segment optical coherence tomography (AS-OCT) characteristics of patients with ocular manifestations of mucopolysaccharidoses type I (Hurler), II (Hunter), and VI (Maroteaux-Lamy). Methods Prospective, observational study of nine consecutive patients with variants of mucopolysaccharidosis (MPS) attending the Paediatric Ophthalmology service at Manchester Royal Eye Hospital, UK. All patients underwent Visante AS-OCT imaging as part of their ophthalmic assessment. Results Ocular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The ocular response analyser, where available, may be used to assess corneal hysteresis, leading to a more reliable measurement of IOP (Fahnehjelm et al 2012a,b). Both ultrasound biomicroscopy and anterior segment OCT may be helpful to assess the anterior chamber angle (Ahmed et al 2014), while the latter technique may also be applied to assess corneal thickness. In addition, posterior segment OCT or ultrasound of the optic nerve can be alternatives for ophthalmoscopy to assess optic disc appearance in patients with MPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ocular response analyser, where available, may be used to assess corneal hysteresis, leading to a more reliable measurement of IOP (Fahnehjelm et al 2012a,b). Both ultrasound biomicroscopy and anterior segment OCT may be helpful to assess the anterior chamber angle (Ahmed et al 2014), while the latter technique may also be applied to assess corneal thickness. In addition, posterior segment OCT or ultrasound of the optic nerve can be alternatives for ophthalmoscopy to assess optic disc appearance in patients with MPS.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal clouding may be present from an early age in MPSI and VI (Ashworth et al 2006;Ferrari et al 2011;. Open-angle glaucoma may be caused by GAG deposits within the trabecular meshwork, causing outflow obstruction, while angle-closure glaucoma may result from changes in anterior segment morphology as a result of GAG accumulation (Ahmed et al 2014). The current literature describes small numbers of MPS patients with glaucoma from single treatment centres with incomplete clinical details, including patients with MPS I (Quigley et al 1975;Spellacy et al 1980;Nowaczyk et al 1988;Mullaney et al 1996), MPS II (Kaiden et al 1982), MPS IV (Cahane et al 1990) and MPS VI (Cantor et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In our patient, SD-OCT showed diffuse hyperreflectivity, uniformly distributed across the entire corneal thickness and associated with increased CCT. Ahmed et al [ 12 ] found OCT to be useful in mucopolysaccharidosis for assessing CCT and anatomy of the iridocorneal angle. Age-dependent increase in CCT was reported in all mucopolysaccharidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior OCT demonstrated open anterior chambers in most of the subjects’ eyes and no iris cysts were found. Anterior OCT was reported to be reliable for measuring the iridocorneal angles and covered a good section of the cornea, despite opacities . According to the literature, the anterior chambers can be more shallow than normal in MPS I .…”
Section: Discussionmentioning
confidence: 99%